Realitas Dakwah Virtual: Efektivitas Serta Etika di Ruang Cyber Inovasi dan Tradisi - Abdul Hamid (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The development of digital technology has brought significant changes in various aspects of life, including in the field of Islamic preaching. The reality of virtual preaching is currently a phenomenon that cannot be ignored, because it has become the main means for preachers to convey Islamic teachings to the wider community through various social media platforms and digital spaces. This study examines the effectiveness and ethics of preaching in cyberspace by emphasizing how technological innovation can blend with the tradition of Islamic preaching that has long been rooted in society. Cyberspace allows for the expansion of the reach of preaching that was previously limited by space and time. With this progress, new challenges arise, especially in terms of delivering messages that must still maintain the principles of Islamic ethics, content accuracy, and social responsibility of preachers. This study uses a qualitative approach with a literature study method. Literature studies were conducted to examine relevant literature related to digital preaching, Islamic communication, and the development of modern communication technology. The results of this study indicate that virtual preaching has a high level of effectiveness in reaching a wider audience, especially young people who are more responsive to digital content that is communicative, concise, and visually appealing. Preachers who are able to combine traditional Islamic values with creative approaches through digital media tend to get positive responses from the audience.